Deputies from the Mogilev province to the State Duma III and IV: social and political characteristics - Lavrinovich, Dmitry S. (Journal of the Belarusian State University. History, 2020)
The article reveals social characteristics of the State Duma deputies. The author shows that due to the censorship nature of the electoral law of 3 June 1907, the deputy corps was dominated by the representatives of the elite groups of population (nobles, large landowners). Besides, the important role was played by the deputies from the church and the officials. Most of them, according to their political views, were supporters of the conservative centre. Deputies focused on the Stolypin’s land reform and the draft law on the introduction of elected zemstvos in the western provinces of the Russian Empire. In 1915, part of deputies of Duma IV from Mogilev province joined the «Progressive coalition», took part in the fight against the tsarist government, and B. A. Engelhardt, as a Chairman of the Military Commission of the Provisional Committee in the State Duma, played an important role during the February Revolution of 1917.